H∞ dynamic observer design for linear discrete-time systems*. Issue 1 (July 2017) - Gao, Nao; Darouach, Mohamed; Alma, Marouane
Abstract: The objective of this paper is to propose a new form of H∞ dynamic observer for linear discrete-time systems. The widely used proportional observer (PO) and proportional integral observer (PIO) can be considered as particular cases of the proposed observer. The observer design is derived from the solution of linear matrix inequalities (LMIs), based on the solutions of algebraic constraints obtained from the unbiasedness conditions of estimation error. A numerical example is provided to show the performance of the proposed observer, compared with PO and PIO.